RISK OF MUSCULOSCELETAL DISORDERS (MSDS) ON TRADITIONAL JEWELRY CREAMERS - Desi Aryani; Yuanita Windusari; Fenny Etrawati (J@ti Undip: Jurnal Teknik Industri, 2021)
The risk of Musculoskeletal Disorders (MSDs) can occur in a variety of occupations including in traditional jewelers. The complaint is caused by an awkward position during work activities. The study aims to identify complaints of Musculoskeletal Disorders (MSDs). This study used qualitative approach through in-depth interviews on 5 key informants and 2 key expert informants and ergonomic risk determination referring to the BRIEF method. The results showed that all informants experienced complaints of the upper neck, lower neck, right shoulder, back, right elbow, right upper arm, and right forearm. Measurements through the BRIEF sheet show that complaints on the left and right elbows, left and right shoulders, neck, and back include high category ergonomic hazards while complaints on the hands and wrists of the right include moderate category ergonomic hazards. High risk of Musculoskeletal Disorders (MSDs) is found at all stages of work (smelting, grinding, posturing, jewelry formation, and gilding). Therefore, workers are recommended to perform muscle relaxation for (8-12 seconds) every half hour.